Basic Principles of the Islamic State: Relevance to the Constitution of the Republic of Indonesia - Aulia Hamdi Dwi Syahroni; Misdin Arifin HM; Abdul Hakim (Jurnal Sahabat ISNU SU, 2025)
The Medina Charter is a formulation of the principles of agreement between the Muslims of Medina under the leadership of the Prophet Muhammad SAW with various non-Muslim groups to build a joint socio-political order. As a political agreement between religious communities, the Medina Charter has several similarities in substance with the 1945 Constitution. Viewed from a material perspective, Pancasila, especially our constitution, the 1945 Constitution and the Medina Charter have several similarities, after the preamble, recognition of equal rights was also included in both, the Medina Charter became a solution to social conflict in the form of religious freedom seen in the Jews who realized cooperation with Muslims to unite. stated in article 25 paragraph 2, namely; "The Jews are free to embrace their religion, as Muslims are free to embrace their religion". In addition, the Indonesian constitution also does the same thing by emphasizing that Indonesia is a unitary state that has a legal basis of Pancasila and the 1945 Constitution as the state structure. It can be seen in article 29 paragraph 2 that it states "The state guarantees the freedom of each resident to embrace their own religion and to worship according to their religion and beliefs."